Signaling Sustainability: Exploring Consumer Perspectives on Communicating Apparel Sustainability Information - Annie Williams; Nancy Hodges (Journal of Sustainable Marketing, 2022)
The fashion industry is characterized by unsustainable production and consumption. However, a consistently noted barrier to sustainable and responsible apparel consumption is a lack of consumer knowledge. A potential solution to mitigate this barrier is to use apparel labeling to signal the sustainability of an item to consumers. Thus, the purpose of this study is to employ signaling theory to explore the aspects of sustainability that resonate with consumers and why, the modes of communication preferred by consumers, and how such information would affect their apparel consumption decisions. In-depth interviews were conducted with a diverse sample of twenty participants. Analysis of the data resulted in the identification of three emergent themes related to communicating information about sustainability that were used to structure the interpretation: Its Importance is Relative, Signal Mode vs. Message, and Increasing the Interest Level. Overall, participants preferred simple, yet detailed messages on apparel labels to communicate aspects of an apparel item’s sustainability. Ultimately, such labeling signals sustainability to consumers, enabling them to differentiate between sustainable and unsustainable apparel.